Strategi Kepala Madrasah Dalam Meningkatkan Prestasi Non Akademik Siswa Melalui Kegiatan Ekstrakurikuler Di MTS Negeri 3 Medan - Fida Mawaddah; Nurika Khalila Daulay; Hendri Fauza (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
This research aims to determine the non-academic achievements obtained by students, existing extracurricular activities, the strategies implemented by madrasah heads to improve students' non-academic achievements, the constraints of madrasah heads in implementing strategies, and the achievements of extracurricular activities in improving students' non-academic achievements at MTs Negeri 3 Medan. This research uses a qualitative type of research with a case study approach conducted in a natural, holistic and in-depth setting. The research subjects were school principals, teachers/extracurricular activity coaches, students, and extracurricular activity coaches. The data collection techniques used were observation, interviews and documentation techniques. The data analysis technique uses the Interactive Analysis Model from Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions or verification. Research data validity techniques are credibility, transferability, dependability and confirmability.The research results obtained are: 1) Students' non-academic achievements come from extracurricular activities that students participate in, including scouts, paskibra, tahfiz, youth scientific work, mujawwad, dance and futsal. 2) The extracurricular activities at MTs Negeri 3 Medan are futsal, paskibra, scouts, KIR, UKS, dance, mujawwad, PIS, band/music, and tahfiz. 3) The strategy implemented by the madrasa head is: selecting competent trainers, determining a good extracurricular schedule, facilities and infrastructure, funding, motivation for students, and evaluation. 4) The obstacles faced by madrasa heads are from the financial side, in terms of time to take part in events or competitions and in terms of when taking part in events that are far away, they have to add supervisor/teacher personnel. 5) Achievement of extracurricular activities is seen from the achievements obtained by students while participating in extracurricular activities, where the non-academic achievements achieved by MTs Negeri 3 Medan students who take part in extracurricular activities have reached the point of participating in and winning national scale events or competitions. Apart from that, the achievements of extracurricular activities can be seen from the impact on the members who take part in them, namely deepening and expanding students' knowledge regarding the extracurricular activities they participate in and succeeding in building students' personalities with strong and independent characters.Thus, the strategy implemented by the head of the madrasa to improve the non-academic achievements of MTs Negeri 3 Medan students through extracurricular activities has been able to provide various achievements in various events or competitions not only between schools or between districts/cities but on a national scale. There are only a few obstacles that need to be addressed by the school, namely from a financial perspective, in terms of time and in terms of distance to participate in events or competitions.